2012
DOI: 10.4236/aces.2012.22027
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Newly Synthesized Aqueous Polyurethane Acrylate Binders for Printing Cotton and Polyester Fabrics

Abstract: The use of the four new synthesized polyurethane acrylate binders in the pigment print paste for screen printing cotton and polyester fabrics and pigment fixation through the polymerization process of the binder by using the thermofixation technique as well as the UV curing technique was studied. The effect of changing time and temperature of thermofixation, and the time of UV curing on the color strength, and prints fastness properties were also studied. The results showed that, the newly synthesized polyuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Typically, in textile coloration, a crosslinked system is obtained by the use of prepolymers with high molecular weight having only one or two acrylate groups . The increase in binder concentration leads to an increase in the number of unsaturated sites of vinyl groups, forming more radicals which are capable of initiating the crosslinking polymerisation of the binder leading to better pigment fixation on the surface upon UV curing, and thus higher colour strength is obtained .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, in textile coloration, a crosslinked system is obtained by the use of prepolymers with high molecular weight having only one or two acrylate groups . The increase in binder concentration leads to an increase in the number of unsaturated sites of vinyl groups, forming more radicals which are capable of initiating the crosslinking polymerisation of the binder leading to better pigment fixation on the surface upon UV curing, and thus higher colour strength is obtained .…”
Section: Resultsmentioning
confidence: 99%
“…El‐Molla et al . synthesised a glycerol ethoxyl‐co‐propoxyl triol‐based, organic solvent‐free water‐borne polyurethane acrylate (PUA) binder . The pigment printing paste prepared with this binder and commercial binders were printed onto cotton and polyester fabrics with the screen‐printing technique and the printed samples were fixed by UV and thermal curing methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They determined the radiation dose from an Hg lamp and found that higher degrees of irradiation led to greater DE colour changes. In another publication, El Molla et al [18] reported the results of static UV irradiation and thermal curing with different binders containing an organic red pigment. Again, a single Hg lamp was used, and washing resistance was visually compared.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the antimicrobial activity of the samples dried by the microwave was better than that of samples obtained by conventional drying. Also, ultraviolet and microwave curing was used by El- Molla et al (2013) to apply new binders for pigment printing of polyester fabrics.…”
Section: Introductionmentioning
confidence: 99%